2003
DOI: 10.1089/152091503763816436
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Plasma Glucose During Rapid Glucose Excursions with a Subcutaneous Glucose Sensor

Abstract: Continuous glucose monitoring has the potential to improve glucose management and reduce the risk of hypoglycemia in individuals with diabetes. Accurate sensors may also allow the development of a closed-loop insulin delivery system. The purpose of this work was to determine the delay time associated with a subcutaneous glucose sensor during rapidly changing glucose excursions. Subcutaneous glucose sensors (Medtronic MiniMed, Inc., Northridge, CA) were inserted in five healthy men. After a 2-h stabilization pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 9 publications
4
63
0
7
Order By: Relevance
“…This finding is in agreement with those from our previous hyperglycaemic clamp studies, which also showed no effect of insulin on the plasma to s.c. ISF glucose gradient or the delay time [7,8]. Taken together, these results imply that s.c. ISF fluid is not derived from tissues that appreciably increase glucose uptake in response to insulin (i.e.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This finding is in agreement with those from our previous hyperglycaemic clamp studies, which also showed no effect of insulin on the plasma to s.c. ISF glucose gradient or the delay time [7,8]. Taken together, these results imply that s.c. ISF fluid is not derived from tissues that appreciably increase glucose uptake in response to insulin (i.e.…”
Section: Discussionmentioning
confidence: 57%
“…Clinical concerns regarding this approach include the lag time in equilibration of glucose across the capillary endothelial barrier [2], possible errors in sensor glucose resulting from changes in the plasma to ISF glucose gradient [3], and protracted recovery times following hypoglycaemia [4,5]. Several groups have suggested that s.c. ISF glucose can fall in advance of plasma glucose if the fall in glucose is due to increased glucose uptake in peripheral tissues [6][7][8] or that the response time may be different for falling vs rising glucose signals [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CGMS has been shown to accurately track rapid changes over a range of interstitial fluid glucose concentrations with an acceptable time lag (21,22). In outpatients, the CGMS has been documented to be an accurate and reliable tool for assessing glycemic stability (23,24).…”
Section: Figure 1-cgms Glucose Values For Patients Without (A) and Wimentioning
confidence: 99%
“…[20][21][22][23] These data showed that the CGMS is very useful to detect postprandial hyperglycemia. Recent data of 91 DM1 patients estimate that the accuracy of the CGMS sensor is more effective in elevated glucose levels than in hypoglycemic state.…”
Section: Discussionmentioning
confidence: 99%